Enhancing childbirth outcomes: The impact of pelvic floor muscle and abdominal exercises - Lina Puspitasari; Raheleh Babazadeh; Misrina Retnowati; Yenni Kristiana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Childbirth is a critical physiological process experienced by women that requires optimal physical and psychological preparation. Inadequate preparation may contribute to prolonged labor and increased pain intensity. Prenatal exercise is recognized as a non-pharmacological approach to improve maternal readiness. A combination of pelvic floor muscle (PFM) exercise and abdominal exercise is considered beneficial for strengthening muscles involved in the labor process, potentially influencing both labor duration and pain perception. Therefore, this study aimed to analyze the effect of combined pelvic floor muscle and abdominal exercises on labor pain intensity and duration of labor among pregnant women. Methods: This study employed a quasi-experimental design with a posttest-only nonequivalent control group approach. The total sample consisted of 60 pregnant women, divided equally into an intervention group and a control group (1:1 ratio). Participants were selected using convenience non-probability sampling. The intervention group received prenatal exercise combining PFM and abdominal exercises starting from 38 weeks of gestation until delivery, while the control group received standard care. Data were analyzed using independent t-tests to compare outcomes between groups. Results: The findings demonstrated that the intervention group had significantly lower mean pain scores compared to the control group at 8 cm cervical dilation (t = -3.828, p = 0.001) and at complete dilation (t = -3.865, p = 0.001). Additionally, the duration of the first stage of labor (t = -3.118, p = 0.003) and the second stage of labor (t = -2.122, p = 0.038) were significantly shorter in the intervention group. Conclusions: Prenatal exercise combining pelvic floor muscle and abdominal exercises has a positive effect on the childbirth process by reducing labor pain and shortening the duration of labor stages. This intervention can be recommended as part of routine antenatal care to improve maternal outcomes.